Avaliação do aprendizado de novas tecnologias da pessoa idosa durante e após a pandemia - Porto, Julyana Scheridan Vicente da Cruz (2024)
This work aims to evaluate possible difficulties and/or ease in learning new technologies by elderly people in Maracanaú, through 2 (two) projects developed in the municipality, during the COVID 19 Pandemic and after this period. The projects are: the Seis Ponto Zero Project (60 years) and the Technological and Social Tea Project, developed at the Elderly Living Center (CCI) and the Institute for Technological and Social Development (IDEAR), respectively. Regarding the specific objectives, we sought to understand the profile of the elderly who participate in the project, understand the influence of ageism, and identify the benefits that this knowledge added to their lives. As for the methodology, the research consists of in depth evaluation with qualitative, exploratory, descriptive, field and bibliographic methodology. Interviews with open questions and filling out Google forms with open and closed questions, and focus groups were also used. The bibliographical survey was carried out through published theoretical references, which supported all parts of this study.